Can the AD-AS model explain the presence and persistence of the underground economy? Evidence from Italy - Gaetano Lisi (Economies, 2021)
The underground economy crucially affects growth and unemployment in both developed and developing countries. Nevertheless, this widespread phenomenon does not appear in the basic model for macroeconomic analysis, namely the Aggregate Demand-Aggregate Supply (or simply AD-AS) model. Therefore, this paper introduces - for the first time, to the best of our knowledge - the underground sector of the economy into the popular AD-AS model, with the aim of increasing its descriptive power. Indeed, the present theoretical extension of the AD-AS model shows that the underground economy - despite its negative effects on aggregate demand and growth - can trigger a supply-side positive shock that mitigates, at least in the short run, the problem of high unemployment. Empirical evidence from Italy is also provided.
Keywords: 330; general aggregative models; informal economy; underground economy